Application of Mime and Pictionary Game Methods on Students' German Vocabulary Mastering - Fadirsair, Paullex; Serpara, Henderika; Akihary, Wilma (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2021)
This research aims to determine the application of using the Mime and Pictionary game methods on the mastery of German vocabulary at SMA Negeri 3 Ambon. This research was carried out at the SMA Negeri 3 Ambon, and the sample was the German learners from class XI MIPA SMA Negeri 3 Ambon, the academic year 2019/2020. This type of research is quasi-experimental research with used one-group pretest-posttest design. The data were analyzed using descriptive techniques and t-test. The results showed that there was an increase in the presentation of German vocabulary mastery before and after the application of the Mime and Pictionary game learning method, from 32% to 46% at an interval of 74-84. Meanwhile, the paired sample t-test results show that sig=0.000< Î±=0.05, which means that there are differences before and after applying the Mime and Pictionary game learning methods. Based on the outcome, it is suggested that this game method, Mime and Pictionary, should be used by German teachers in German lessons.